2017
DOI: 10.1371/journal.pone.0177964
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic silence of pleiotrophin by targeted delivery of siRNA and its effect on the inhibition of tumor growth and metastasis

Abstract: Pleiotrophin (PTN) is a secreted cytokine that is expressed in various cancer cell lines and human tumor such as colon cancer, lung cancer, gastric cancer and melanoma. It plays significant roles in angiogenesis, metastasis, differentiation and cell growth. The expression of PTN in the adult is limited to the hippocampus in an activity-dependent manner, making it a very attractive target for cancer therapy. RNA interference (RNAi) offers great potential as a new powerful therapeutic strategy based on its highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…High PTN expression reportedly contributes to cell metastasis, at least in part through effects on the activities of metal matrix proteases (MMPs) [10]. We used Transwell assays (with or without Matrigel) to study the effect of miR-627-3p on osteosarcoma metastasis (Figure 4A–4D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High PTN expression reportedly contributes to cell metastasis, at least in part through effects on the activities of metal matrix proteases (MMPs) [10]. We used Transwell assays (with or without Matrigel) to study the effect of miR-627-3p on osteosarcoma metastasis (Figure 4A–4D).…”
Section: Resultsmentioning
confidence: 99%
“…Less is known about the role of miR-627 in osteosarcoma and the mechanism through which it acts. PTN is highly expressed in various types of cancer, including melanoma, breast cancer, glioma, prostate cancer, leukemia, choriocarcinoma and lung cancer, where it appears to play a critical role in mediating angiogenesis, tumor cell proliferation and metastasis [10]. Studies have shown that PTN may be a reliable prognostic indicator in osteosarcoma patients, and inhibitors of PTN could potentially improve chemotherapeutic efficacy in patients with unresponsive and recurrent osteosarcoma [9].…”
Section: Discussionmentioning
confidence: 99%
“…PTN, also known as heparin-binding growth-associated molecule, is a 136-amino acid secreting growth/differentiation cytokine that is developmentally regulated [ 30 ]. PTN was found to be up-regulated in various types of human cancers, and overexpression of PTN was suggested to promote cell proliferation and angiogenesis, contributing to cancer progression [ 31 33 ]. Recent study also demonstrated the concentration in the fine-needle aspiration thyroid tissues was increased PTC [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…MEIS1 might limit the proliferation of non-small-cell lung adenocarcinoma ( 34 ) and was described methylated in squamous cell carcinomas ( 35 ). PTN is highly expressed in embryonic and postnatal development, while it is quite down-regulated in adult life; however, it is strongly expressed in lung tumor and other types of cancer ( 36 ). Hypermethylation was found in our samples for the DMR close to MEIS1 and PTN.…”
Section: Discussionmentioning
confidence: 99%